Efficacy of Tribenuron Alone and Following Preemergence Herbicides in Tribenuron‐Resistant Sunflower. Issue 1 (21st June 2013) - Godar, Amar S.; Stahlman, Phillip W.; Dille, J. Anita
Abstract : Field experiments were conducted near Hays, KS, USA in 2007 and 2008 to assess the effectiveness of postemergence (POST)‐applied tribenuron‐methyl (tribenuron hereafter) with and without preemergence (PRE) herbicides in tribenuron‐resistant sunflower. Treatments consisted of two rates of tribenuron (9 and 18 g ai/ha) alone and labeled rates of PRE‐applied pendimethalin, sulfentrazone, or S ‐metolachlor followed by tribenuron POST at 9 and 18 g/ha. Tribenuron with PRE herbicides provided little or no better control of kochia, puncturevine, or Russian thistle compared to tribenuron alone. However, tribenuron following PRE sulfentrazone at 140 g/ha or S ‐metolachlor at 1400 g/ha improved tumble pigweed control by at least 13% compared to tribenuron alone both years. Tribenuron treatments in 2007 caused temporal chlorosis and stunting but did not affect crop height at R5 stage. Either rate of tribenuron following sulfentrazone or S ‐metolachlor produced the highest yield ranging from 1940 to 2010 kg/ha. The small improvement in control of some species achieved with PRE‐POST treatments likely was not enough to off‐set the additional cost compared to results of a timely application of tribenuron at full rate. However, PRE herbicide use reduces the risks of weed competition resulting from untimely POST applications and of tribenuron not controlling ALS‐resistant weed biotypes.